G231 A study to determine whether changes in the system of caring for children and young people in a same day admission unit could improve quality of care without adversely effecting theatre utilisation. (27th April 2015) - Stuart, C
Abstract : Background: The same day admissions unit (SDAU) was formerly an open ward area with no systems in place for admitting up to 45 children a day. No children with learning disabilities were cared for on the unit because it was seen as unsuitable due to the noise and lack of space. In March 2014 the new SDAU opened with 16 cubicles and a large playroom. This offered the opportunity to be able to bring in systems that would improve quality of care for patients. Admissions were staggered and fasting times were tailored to the admission times to ensure that children were fasted for less time and had less time to wait. We also began to accept Children with learning disabilities onto the unit. The staggered admissions however meant forced breaks in theatre lists. Aims: To examine whether a bringing in an organised system of care was successful in increasing the quality of care to patients and their families without adversely impacting on theatre utilisation. The main areas of focus were: Patient privacy and dignity, family waiting times, fasting times, family levels of stress and anxiety and being able to provide an improved service for children with learning disabilities. Method: Quantitative data was taken of "patient status at a glance" and PIMS to examine whether fasting and waiting times had been reduced by the new system. The number of patients going through both units was also compared. Using a questionnaire patient's and their families were able to evaluate their experiences of the new SDAU and compare this with the old unit if they had visited both. Results: The system changes were measured and showed a decrease in waiting and fasting times. Patients and families find the new unit to be calmer and more organised than the old ward and prefer to be cared for in individual cubicles. Children with learning disabilities are being routinely admitted via SDAU. Conclusions: Good planning involving all the staff was crucial to the change being successful. Communication and using planned and practiced systems was also key. Regular reviewing of systems and being prepared to change them was crucial. The process is still evolving.